IMPLIKASI POLITIK HUKUM KEIMIGRASIAN INDONESIA DALAM PEMBATASAN PERLINTASAN TERHADAP PEMULIHAN EKONOMI PASCA KEADAAN DARURAT COVID-19 - Ika Wahyuni; Mahmul Siregar; Detania Sukarja; Mirza Nasution (Halu Oleo University, 2025)
This research analyses the legal politics of Indonesia's immigration policy during and after the COVID-19 pandemic in the context of national economic recovery. By employing a normative juridical method with a conceptual and statutory approach, the study explores how legal instruments such as visa restrictions and movement control served as tools to protect national security and public health, while also impacting state revenue from the non-tax sector. The results show that post-pandemic immigration policy was strategically adapted to optimise economic functions, such as through the implementation of selective visa policies and innovations like the